HUBUNGAN TINDAKAN PERSONAL HYGIENE IBU DENGAN KEJADIAN DIARE PADA BALITA DI PUSKESMAS BILALANG KOTA KOTAMOBAGU - Mokodompit, Amanda; Ismanto, Amatus Yudi; Onibala, Franly (JURNAL KEPERAWATAN, 2015)
Abstract : Diarrheal disease is still a public health problem in this development country such as Indonesia, because moritility anda mobidility are still high. Diarrhea is the second cause among toddler after pneumonia. Low coverage o personnel hygiene and enviromental sanitation oten a risk factor for the occurene of diarrhea’s outbreaks. National data issued by the health department of Indonesia said that every year thera are 100.000 children died o diarrhea. The aim is to determine the relationship ith the mother’s personnel hygiene measures the incidence of diarrhea in infants at health center working area Bilalang Kota Kotamobagu. Research design is cross sectional. Population is all of toddler are experiencing of diarrhea at health center working area Bilalang. Sample o Research are 42 respondents. Research’s Result are statical test chi square test at the signiacance level at 95% (α 0,05), indicating that there is a relationship between maternal personnel hygiene measures ith the incidence of diarrhea on toddler ith p value = 0,001 < 0,05. Conclusion o this research is realtionship beteen maternal personnel hygiene actions with diarrhea o p value < α = 0,05.Keywords : Keywords:Diarrhea, Personnel Hygiene, ToddlerAbstrak : Penyakit diare masih merupakan masalah kesehatan masyarakat di Negara berkembang sepeti Indonesia, karena mortilitas dan morbiditas yang masih tinggi. Diare adalah penyebab kematian yang kedua pada anak balita setelah pneumonia. Rendahnya cakupan personal hygiene dan sanitasi lingkungan sering sekali menjadi faktor resiko terjadinya KLB diare. Data nasional yang dikeluarkan Departemen Kesehatan Repulbik Indonesia menyebutkan setiap tahunnya di Indonesia 100.000 balita meninggal dunia karena diare. Tujuan untuk mengetahui hubungan tindakan personal hygiene ibu dengan kejadian diare pada balita di puskesmas bilalang kota kotamobagu. Desain Penelitian Cross Sectional. Populasi adalah semua balita yang mengalami diare di puskesmas bilalang. Sampel penelitian adalah 42 responden. Hasil Penelitian uji statistik uji Chi Square pada tingkat kemaknaan 95% (α=0,05), menunjukkan bahwa ada hubungan antara tindakan personal hygiene ibu dengan kejadian diare pada balita dengan nilai p value = 0,001 < 0,05. Kesimpulan dalam penelitian ini ada hubungan antara tindakan personal hygiene ibu dengan kejadian diare dengan nilai p value < α=0,05.Kata Kunci: Diare, Personal Hygiene, Balita